Antihyperglycemic Effectiveness Test of 96% Ethanol Extract of Nutmeg (Myristica fragrans Houtt.) Stem Bark in Streptozotocin-Induced Mus musculus - Nirwana Putri Mastur; Nurfitria Junita (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by an increase in blood glucose levels. The bark of nutmeg (Myristica fragrans Houtt.) is known to have antihyperglycemic potential because it contains bioactive compounds such as flavonoids, alkaloids, tannins, and saponins. The nutmeg plant has benefits as an antidiabetic, antifungal, and antibacterial agent. Objective: This study aimed to evaluate the effectiveness of 96% ethanol extract of nutmeg bark as a blood glucose-lowering agent in male mice (Mus musculus) induced with streptozotocin. Method: This experimental research was conducted on 25 mice using a randomized design, divided into five groups of five mice each. The material was extracted using the maceration method with 95% ethanol. Results: Diabetes in mice was induced with streptozotocin at a dose of 40 mg/kg BW. Group I received 1% Na-CMC (negative control), Group II received glibenclamide (positive control), and Groups III–V received ethanol extract of nutmeg bark at doses of 50, 100, and 200 mg/kg BW, which reduced glucose levels by 11.3%, 12.7%, and 13.9%, respectively. One Way ANOVA analysis showed a p value < 0.05, indicating a significant difference in blood glucose reduction among the concentrations of 96% ethanol extract of nutmeg bark. Conclusion: The 96% ethanol extract of nutmeg bark has been proven to have an antihyperglycemic effect, with the most effective dose at 200 mg/kg BW.Bottom of Form.